2001
DOI: 10.1073/pnas.081615298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the antitumor activity of antiangiogenic proteins delivered by gene transfer

Abstract: Although the systemic administration of a number of different gene products has been shown to result in the inhibition of angiogenesis and tumor growth in different animal tumor models, the relative potency of those gene products has not been studied rigorously. To address this issue, recombinant adenoviruses encoding angiostatin, endostatin, and the ligand-binding ectodomains of the vascular endothelial growth factor receptors Flk1, Flt1, and neuropilin were generated and used to systemically deliver the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
244
3
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(258 citation statements)
references
References 31 publications
9
244
3
2
Order By: Relevance
“…Indeed, we detected the presence of endostatin in the livers of intratumorally ES -transduced mice, but not in the controls, on day 7 after the transduction using genomic PCR ( data not shown ). Recently, Kuo et al 38 reported that tail vein injections of recombinant adenoviruses encoding endostatin and angiostatin produced only a modest growth inhibition in a few subcutaneous murine tumor models. Also, the levels of systemic endostatin required for antitumor effect have displayed great variations ranging from low 32 to high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we detected the presence of endostatin in the livers of intratumorally ES -transduced mice, but not in the controls, on day 7 after the transduction using genomic PCR ( data not shown ). Recently, Kuo et al 38 reported that tail vein injections of recombinant adenoviruses encoding endostatin and angiostatin produced only a modest growth inhibition in a few subcutaneous murine tumor models. Also, the levels of systemic endostatin required for antitumor effect have displayed great variations ranging from low 32 to high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Kuo et al 17 and De Bou¨ard et al 32 suggested that the soluble form of Flk-1, Flt-1 and INF-a possessed significantly more potent antitumor activity than angiostatin or ES when delivered via gene transfer. A likely explanation for this diminished effect is an insufficient concentration of the antiangiogenic factors at the tumor site because of their short half-life in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the antitumor effects that follow antiangiogenic gene delivery from a variety of viral and non-viral vectors in vivo highlight the potential of antiangiogenic gene therapy as an additional strategy for treatment against cancer and metastatic dissemination. 10,16,17 We chose the highly efficient adenovirusbased gene delivery system to evaluate the antitumor potency of several conjugates between HSA and antiangiogenic factors (K1-3, ES, ATF and Can) in TRP-1/ SV40Tag transgenic mice, which spontaneously develop eye tumors with brain metastases. 18 Here, we present, for the first time, a comparative study of the antimetastatic and antiangiogenic activities of these fused factors in a metastatic ocular tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include TIMP-3, 78 angiostatin, endostatin, 79 platelet factor-4, 80 thrombospondin-1, 81 soluble extracellular domains of growth factor receptors such as Flt-1 82 and FGF-R 83, including fusion proteins containing the Fc portion of antibodies such as Flk1-Fc, 79 sNeuropilin-1-Fc, 84 and intrabodies that block Tie-2 receptor surface expression. 85 All these anti-tumour angiogenesis strategies using adenovirus as a vector showed a significant reduction in tumor angiogenesis and tumor growth, except for endostatin and angiostatin.…”
Section: Antiangiogenic Gene Therapy Expressed In Non-endothelial Cellsmentioning
confidence: 99%
“…85 All these anti-tumour angiogenesis strategies using adenovirus as a vector showed a significant reduction in tumor angiogenesis and tumor growth, except for endostatin and angiostatin. 79 Combination of antiangiogenic factors has shown synergistic effects. 80 Non-viral vectors such as liposomes that do not have a natural target and can transduce many cell types have been also employed as vectors for anti-angiogenic gene delivery.…”
Section: Antiangiogenic Gene Therapy Expressed In Non-endothelial Cellsmentioning
confidence: 99%